PEMODELAN MATEMATIKA SEBAGAI KERANGKA ANALITIS DALAM PENENTUAN NISAB ZAKAT MAL - Firdaus, Ira; Tohir, Mohammad; Asyari, Dian Noer (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2025)
Zakat Mal, as one of the pillars of Islam, plays a strategic role in maintaining the social and economic balance of the community. However, public understanding of calculating the nishob of Zakat Mal is often still limited, so a more systematic and applicable approach is needed. This study aims to analyze the calculation of nishob of Zakat Mal using mathematical modeling as a bridge between fiqh studies and numerical methods. The research method used is a Systematic Literature Review (SLR) with thematic analysis, identifying recurring patterns from various studies, and utilizing sources such as journals and the Book of Fathul Qorib Mujib. The results of this study successfully present a systematic mathematical modeling for calculating the nishob of Zakat Mal, including Zakat on livestock (camels, cows, goats), gold, silver, and agricultural products. This modeling uses basic concepts of numbers, arithmetic operations, multiplication, and linear functions. In conclusion, mathematical modeling in calculating the nishob of Zakat Mal is very appropriate, providing great benefits in facilitating Muzaki and amil Zakat and increasing students' understanding and interest in integrating mathematics and Fiqh in education. Moreover, mathematical modeling not only provides practical solutions in the distribution of Zakat obligations but also contributes to strengthening numerical literacy in the religious field and opens up opportunities for developing a digital Zakat system in the modern era.